Mix Code and instead code in the process of learning in Class VII MTS NW Mengkuru Years Lessons 2014/2015 - Mohzana, Mohzana (VELES Voices of English Language Education Society, 2017)
This research aims to know the shape of the mix of code, form over the code and the factors behind their occurrence mix code and over the code. This research data is data written. Data collection is done by using the technique of observation, interview techniques or discussion and recorded techniques. The results obtained from these techniques are: (1) mix the code obtained i.e. shape mix code in the form of words and forms of intervention code be phrase, (2) besides over code obtained i.e. form over the code from the language of Arab to the Indonesian language and shapes instead of code Indonesian into  Sasak language, (3) factors-factors which aspects influenced the occurrence of interfering factors of habit, i.e. code limitations mastery Indonesian language is good and right, situation, and forgetten factor. As for factors which aspects influenced the occurrence over the code factors mastery language Indonesia, habits, said opponents and speakers. Based on these findings, it can be concluded that the mixed form of code that is in the form of words and phrase. While shape instead of a language code from Arab to the Indonesian language, from Indonesia language into Sasak language. Hence factor of occurrence of mixed code i.e. habit, limitation on mastery of the Indonesian language is good and right, situation, and forgetten factor. And factors the occurrence the occurrence over code that is mastery of Indonesia language, habit, lsaid clouds and speaker.